2020
DOI: 10.1038/s41598-020-60538-w
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis and luminescence properties of core-shell-shell structured SiO2@AIPA-S-Si-Eu@SiO2 and SiO2@AIPA-S-Si-Eu-phen@SiO2 nanocomposites

Abstract: open Scientific RepoRtS | (2020) 10:3522 | https://doi.org/10.1038/s41598-020-60538-w www.nature.com/scientificreports www.nature.com/scientificreports/ Over the years, though the core-shell structured nanocomposite with silica coating inorganic materials were successive studied [17][18][19] , but their weaker luminescent properties limit their application in many fields. However, the rare earth organic complexes have excellent luminescence properties, which the energy of the organic ligands was efficiently tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…Based on the EDX spectra (Figure S3) and their corresponding atomic ratios (Table S1), the approximated atomic ratios of Si and Al of 1:0, 2:1, 1:1, and 0:1 can be obtained, denoting the samples as QDs@SiO 2 , QDs@SiO 2 @AlO X -(2:1), QDs@SiO 2 @AlO X -(1:1), and QDs@AlO X , respectively. Moreover, Fourier transform infrared (FT-IR) spectra revealed that the Si–OH characterized peaks at 952 cm –1 became weaker with increasing proportions of the AlO X layer on the SiO 2 surface (Figure b) . In addition, in the high-resolution XPS spectra of Si 2p in Figure S4a, signals were associated with the Si–O–Si bond at the binding energy of 103.57 eV (QDs@SiO 2 ) and the Si–O–Al bond at 102.02 eV. , In the case of increasing AlO X proportion, the Si–O–Si bond decreased and the Si–O–Al bond became dominant in QDs@SiO 2 @AlO X -(2:1) and QDs@SiO 2 @AlO X -(1:1), respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Based on the EDX spectra (Figure S3) and their corresponding atomic ratios (Table S1), the approximated atomic ratios of Si and Al of 1:0, 2:1, 1:1, and 0:1 can be obtained, denoting the samples as QDs@SiO 2 , QDs@SiO 2 @AlO X -(2:1), QDs@SiO 2 @AlO X -(1:1), and QDs@AlO X , respectively. Moreover, Fourier transform infrared (FT-IR) spectra revealed that the Si–OH characterized peaks at 952 cm –1 became weaker with increasing proportions of the AlO X layer on the SiO 2 surface (Figure b) . In addition, in the high-resolution XPS spectra of Si 2p in Figure S4a, signals were associated with the Si–O–Si bond at the binding energy of 103.57 eV (QDs@SiO 2 ) and the Si–O–Al bond at 102.02 eV. , In the case of increasing AlO X proportion, the Si–O–Si bond decreased and the Si–O–Al bond became dominant in QDs@SiO 2 @AlO X -(2:1) and QDs@SiO 2 @AlO X -(1:1), respectively.…”
Section: Resultsmentioning
confidence: 96%
“…The AMP-ZnONPs spectra showed the characteristic absorption peaks of ZnONPs, KH550 and AMP. In addition, the signal in 1058.9 cm –1 was mainly assigned to the stretching vibration of the C-O-C group, the absorption peak at 1,629 cm –1 corresponded to N-H stretching vibrations ( 39 , 40 ). FT-IR spectra of AMP showed that the band at 1636.2 cm –1 corresponding to the C = O bond ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect partially solves the mentioned issues, assuring a proper separation among the emitting units and hindering the formation of aggregates as well as preserving low-temperature, thanks to the increased distance from the p-n junction. Another option is to protect the organic core with an external mesh (inorganic) to increase the stability against the environmental conditions and the photogeneration of surface groups [92,93]. On the other hand, the concentration quenching effect hampers a large amount of organic compound and the resistance at high luminous flux can decrease the stability of the devices.…”
Section: Session 5: Beyond Rare-earth Elements In White Ledmentioning
confidence: 99%